Religion and Globalization: Fátima and the hallmarks of a global cartography - Duarte, Marco Daniel (2024)
The devotional network formed around the typical religious practices of the Cova da Iria Sanctuary in Fátima, in central Portugal, allows us to speak of a psychological geography marked by interculturality. Devotion to our Lady of Fatima therefore bears several marks of a global cartography, which can be gauged from different categories: geographical territory, symbolic territory, spiritual territory, political territory, economic territory, social territory and intellectual territory. The phenomenon of Fátima, over the course of a century, therefore leads us to a set of taxonomies that the Human and Social Sciences will have to map. In this essay, we lay down clues and present relevant data to develop this scientific journey.